Theoretical aspects of computing -- ICTAC 2018 : 15th International Colloquium, Stellenbosch, South Africa, October 16-19, 2018, Proceedings /: 15th International Colloquium, Stellenbosch, South Africa, October 16-19, 2018, Proceedings. (2018) - Unknown
No abstract available